A numerical investigation of the hydrodynamic and mass transfer behavior of a liquid-liquid semi-partition bioreactor (SPB) designed for in-situ extractive fermentation. (16th January 2023) - Teke, George M.; Gakingo, Godfrey K.; Pott, Robert W.M.
Highlights: A CFD model for a multiphase semi-partition bioreactor (SPB) is developed. The hydrodynamics and mass transfer within the multiphase SPB are investigated. Results show need for minimum agitation speed for homogeneity in mixer section of SPB. Results affirm the SPB works by liquid-liquid partitioning, phase separation and extraction. Abstract: Organisms used in fermentation processes are sometimes inhibited by accumulation of products or by-products. One route to circumvent this is via extractive fermentation. To facilitate this, novel bioreactor designs are required, such as the semi-partition bioreactor (SPB) which has been designed for in-situ extractive fermentation. This study reports on the numerical investigation of an SPB, considering phase separation, hydrodynamics and mass transfer behaviour. Key findings illustrate that a minimum agitation speed is necessary to attain system homogeneity in the mixer section. Furthermore, the results indicate that the working principle of the bioreactor will be effective for liquid-liquid partitioning and mass transfer followed by flux exchange between the mixer and settler sections and subsequent phase separation in the settler section. This mechanism has a shorter characteristic time than the replenishment of the bioreactor with recycled (and back-extracted) extractant. The reactor thus shows promise as a route for fermentations susceptible to product inhibition.